2021
DOI: 10.1177/1420326x211011698
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model of polycyclic aromatic hydrocarbon quarterly emissions based on GDP from a government policy perspective

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a kind of carcinogenic, teratogenic and mutagenic pollutants that exist widely. In this study, a quarterly emission inventory of 16 PAHs listed as the US EPA priority pollutants was established by using the emission factor (EF) method. The results showed that the distribution of PAHs in different industries varied greatly with different year and quarter. The main characteristics of PAHs seasonal emission are that Q1 emission is the most and Q4 emission is the least. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…9,10 PAHs belong to a group of semi-volatile organic compounds (SVOCs) and occur as gaseous and particulate phases and as deposited dust. [11][12][13][14][15][16][17] They are typically generated during incomplete combustion, mainly under conditions of high humidity and insufficient temperature and oxygen. 18,19 PAHs with 2-4 aromatic rings occur in the gaseous phase, whereas PAHs with 4-6 aromatic rings exist in the particulate phase.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 PAHs belong to a group of semi-volatile organic compounds (SVOCs) and occur as gaseous and particulate phases and as deposited dust. [11][12][13][14][15][16][17] They are typically generated during incomplete combustion, mainly under conditions of high humidity and insufficient temperature and oxygen. 18,19 PAHs with 2-4 aromatic rings occur in the gaseous phase, whereas PAHs with 4-6 aromatic rings exist in the particulate phase.…”
Section: Introductionmentioning
confidence: 99%
“…Since various products containing SVOCs are regularly used within an indoor environment, epidemiological and toxicological studies on their potential adverse impacts on the health of indoor residents have been reported. [4][5][6] For instance, in 2005, the National Institute of Advanced Industrial Science and Technology (AIST) published a detailed DEHP risk assessment in Japan. 7 According to this risk assessment, DEHP intake occurs primarily via ingestion of food products, with the highest assumed intake for 1-year old children being 21.7 μg/kg/d.…”
Section: Introductionmentioning
confidence: 99%